Investigating strategies for involving host mining communities in mine closure planning: an integrated stakeholder engagement in the West Rand, South Africa - Majela, Karabelo Innocent (Department of Environmental and Geographical Science, 2025)
Sustainability challenges are intricate and interconnected and require a collaborative effort from multiple stakeholders. There is an increased accountability for mining companies to implement socially responsible strategies to curb environmental, social and economic impacts in societies, particularly within the context of mine closure and host mining communities. This is primarily because these impacts are disproportionately felt at the community level. Responsible mining practices are equally crucial in addressing these impacts. These practices include social and environmental assessments, transparency, and compliance with international standards, which ensure that mining operations do not compromise the well-being of local communities and ecosystems. By integrating responsible mining principles, mining companies can mitigate adverse impacts and contribute to sustainable development. Literature also highlights that industry best practices continues to promote the need to engage host mining communities in mine closure planning and processes through stakeholder engagement. Effective stakeholder engagement not only fosters collaboration and innovative outcomes but also ensures that responsible mining practices are upheld, thereby promoting long-term sustainability and community well-being. However, despite this, there is a gap in knowledge on continuous community consultation in mine closure planning through stakeholder engagement. This includes the practical application of the integration of host mining communities in mine closure planning and maintaining ongoing stakeholder engagement with communities. Additionally, the lack of integration of host mining communities is exacerbated by unclear regulatory frameworks that create legislative loopholes for mining companies to treat and maintain stakeholder engagements as an optional administrative activity. Thus, this research uses the West Rand area to enhance the understanding of the impacts of mine closure on host mining communities. This is done to recommend strategies that could potentially improve the integration of host mining communities into mine closure plans within the South African context. To realise the above-stated aim, the study was conducted through a qualitative research approach using thematic content analysis based on four primary research questions: (1) What are the impacts of mine closure in mining host communities in the West Rand Region? (2) How do legislative uncertainties influence the decision-making of mining companies concerning mine closure and integration of host mining communities in closure plans? (3) What is the level of communication transparency between host mining communities and mining companies in the West Rand? and (4) What are the existing integration strategies for the inclusion of host mining communities into closure plans in the West Rand? The findings reveal that the impacts of mine closure cuts across the three pillars (environmental, social and economic) of sustainable development. The evaluation of these impacts should take place using a cascading approach. Secondly, the current legislation is ineffective due to institutional capacity, legislative gaps and a phenomenon called revolving door, a mechanism for captured state institutions. Thirdly, there is miscommunication between mining companies and communities due to a lack of established mining community structures, high community illiteracy levels, and the use of technical language in reports. Lastly, existing engagement strategies by mining companies in the West Rand are still ineffective due to selective engagement, lack of feedback monitoring, and lack of clarity and purpose in meetings. Therefore, the study proposes a constructive and proactive stakeholder engagement framework that promotes collaboration and ongoing engagements with host mining communities while elucidating and recommending reforms to the existing legislative ambiguities that hinder ongoing stakeholder engagement, the inclusion of host mining communities and the sustainable closure of mines.